The factors influencing the quality of care in a residential institution - Вонберг, Т. В.; Давидюк, Е. А. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2018)
The relevance of the problem study was proved. Factors influencing the quality of service at an orphanage institution were determined. The factors are grouped into groups: external factors of macro level, internal factors of meso-level and internal factors of the microlevel. The influence of each of the factors on quality has been investigated. Prospects for further research on identified factors were identified.